KONSEP DIRI PADA ODHA ATAS KOMUNITAS ODHA DI LSM VICTORY PLUS YOGYAKARTA - Rianiate Manik; Titik Muti'ah Muti'ah (JURNAL SPIRITS, 2012)
ABSTRACTHIV and AIDS is a disease that is very dangerous for humans. Iumans by nature have a self-concept that can work consciously or consciously, that can give purpose and direction to behavior. Actually, he concept itself is considered as a cognitive component of social self as z whole, which provides an explanation of how individuals understand the 5ehavior, emotion, and motivation alone. Self-concept greatly affect how a 9erson's life and confront of this study was to determine the extent to which the concept of self in People Living With HIV and AIDS (PLWHA). Research subjects to be studied four people living with HIV with the characteristics of two men and two women aged 23-37 years in Victory Plus Yogyakarta.In this study using qualitative methods interviews and observation. Technical analysis of the data used is data reduction, data display, conclusion triangulation and verification. Based on the research showed that four subjects had a positive self-concept. It can be seen through physical self-concept, personal self-concept, social self-concept, the concept of moral and ethical self, family self-concept, academic self-concept. Supporting factors also affect the self-concept that is the subject of the four factors of age, education, the environment, in this study the main supporting factor is the most influential organization as the place to work PLWHA.Keywords: HIV and AIDS, self-concept, People Living With HIV